1994
DOI: 10.1103/physrevb.49.14066
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of reduced shot noise in a diffusive mesoscopic conductor

Abstract: We demonstrate that a diffusive narrow wire of a length much longer than the elastic scattering length and the phase-coherence length, but of the order of the energy relaxation length, exhibits shot noise with an intensity lower than the full shot-noise level. At 4.2 K, the reduction factor is shown to vary between 0.2 and 0.45, depending on the width of the wire. The reduction is consistent with recent theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 14 publications
4
67
0
Order By: Relevance
“…These predictions were also confirmed experimentally on quantum point contacts, diffusive conductors, resonant tunneling diodes and SETs. [13][14][15][16] However, the situation if ferromagnetic junctions significantly differs from that in nonmagnetic SETs and to our best knowledge there is neither experimental nor theoretical work published up to now on shot noise in ferromagnetic SETs. As we show in this paper, large spin fluctuations, which occur in ferromagnetic junctions, have a significant influence on the shot noise, particularly at low frequencies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These predictions were also confirmed experimentally on quantum point contacts, diffusive conductors, resonant tunneling diodes and SETs. [13][14][15][16] However, the situation if ferromagnetic junctions significantly differs from that in nonmagnetic SETs and to our best knowledge there is neither experimental nor theoretical work published up to now on shot noise in ferromagnetic SETs. As we show in this paper, large spin fluctuations, which occur in ferromagnetic junctions, have a significant influence on the shot noise, particularly at low frequencies.…”
Section: Introductionmentioning
confidence: 94%
“…In the case of nonmagnetic SETs this problem was recently extensively studied in the relevant literature. [7][8][9][10][11][12][13][14][15][16] It has been shown that the noise can provide additional information on the electronic structure, transport properties and also on electron-electron interactions. A special issue is the problem of suppression of the zero-frequency shot noise by electron correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, shot noise in metallic diffusive wires was investigated by Liefrink et al [79], who observed that it is suppressed with respect to the Poisson value. The suppression factor in this experiment lies between 0.2 and 0.4 (depending on gate voltage).…”
Section: Metallic Diffusive Wiresmentioning
confidence: 99%
“…Expressions (79) and (80) are valid in the linear and non-linear regimes, provided interactions are not important. We will consider the noise in the non-linear regime in Section V, where it will be shown that effects of charging of the well may play an important role.…”
Section: Resonant Tunnel Barriersmentioning
confidence: 99%
See 1 more Smart Citation